2011
DOI: 10.1590/s0102-695x2011005000007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antinociceptive activities of Euterpe oleracea Mart., Arecaceae, oil

Abstract: Abstract:The oil of the fruits of Euterpe oleracea Mart., Arecaceae (OEO), was evaluated in models of inflammation and hyperalgesia in vivo to study its effects on these conditions. The experimental models contained the writhing test in mice, rat paw edema, granuloma test in rats, vascular permeability in rats, cell migration to the peritoneal cavity in rats and ear erythema induced by croton oil in mice. Doses of 500, 1000 and 1500 mg/kg of OEO were administered orally. The observed number of writhes was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 39 publications
2
35
0
7
Order By: Relevance
“…Favacho et al (2011) also reported the presence of the fatty acids, oleic, palmitic, and palmitoleic compounds as the major constituents of the açaí fruit oil. According to Del Pozo-Insfran et al (2004), the presence of bioactive substances, such as phenolic acids, flavonoids, and anthocyanins, attributes antioxidant properties and antitumorigenic potential to this fruit.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Favacho et al (2011) also reported the presence of the fatty acids, oleic, palmitic, and palmitoleic compounds as the major constituents of the açaí fruit oil. According to Del Pozo-Insfran et al (2004), the presence of bioactive substances, such as phenolic acids, flavonoids, and anthocyanins, attributes antioxidant properties and antitumorigenic potential to this fruit.…”
Section: Introductionmentioning
confidence: 92%
“…This fruit is also used in folk Brazilian medicine to treat anemia, diarrhea, malaria, pain, inflammation, hepatitis, and kidney diseases (Leão et al, 2007;Souza et al, 2011;Caetano et al, 2014;de Bem et al, 2014;Vásquez et al, 2014). Specific açaí fruit oil therapeutic potentials regarding anti-inflammatory, antinociceptive, and antidiarrheic activities were reported (Plotkin and Balick, 1984;Favacho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits can be natural sources of antioxidants such as vitamins (Oliveira et al, 2011;Leong and Oey, 2012), carotenoids (Souza et al, 2014;Valdivielso et al, 2015) and phenolic compounds (Kang et al, 2012;Paz et al, 2015) with antioxidant properties (Castrejón et al, 2008;Koca and Karadeniz, 2009;Kang et al, 2012). The antioxidant activity of these compounds may act at different stages in the oxidation process, lowering free radicals concentration, chelating ions and even decomposing primary products and leading to nonradical compounds (Lobo et al, 2010;Perera et al, 2016) which help balance the immune system (Kang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…is a perennial species that is widely distributed in the Amazon. Its natural habitat are the floodplains along the Amazon estuary in the state of Pará, Brazil, where it has several uses (Menezes et al, 2008;Favacho et al, 2011). Pará is the main producer and consumer of acai (Farias Neto et al, 2012), which is usually served as a drink obtained from fresh and in natura pulp extracted from the fruit.…”
Section: Introductionmentioning
confidence: 99%